2011
DOI: 10.1371/journal.pone.0025097
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Roles of Endogenous Brain-Derived Neurotrophic Factor, TrkB and Sortilin in Colorectal Cancer Cell Survival

Abstract: BackgroundNeurotrophin receptors were initially identified in neural cells. They were recently detected in some cancers in association with invasiveness, but the function of these tyrosine kinase receptors was not previously investigated in colorectal cancer (CRC) cells.Methods and FindingsWe report herein that human CRC cell lines synthesize the neural growth factor Brain-derived neurotrophic factor (BDNF) under stress conditions (serum starvation). In parallel, CRC cells expressed high- (TrkB) and low-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 64 publications
11
85
1
1
Order By: Relevance
“…In our recent study, the proBDNF/p75NTR pathway appeared to inhibit malignant glioma cell growth and migration (13). A recent report also showed that proBDNF suppressed the growth of colorectal cancer cells (14). Therefore, we postulated that the mature form of BDNF plays a supportive role in the growth and migration of tumour cells.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In our recent study, the proBDNF/p75NTR pathway appeared to inhibit malignant glioma cell growth and migration (13). A recent report also showed that proBDNF suppressed the growth of colorectal cancer cells (14). Therefore, we postulated that the mature form of BDNF plays a supportive role in the growth and migration of tumour cells.…”
mentioning
confidence: 71%
“…However, few studies were able to distinguish mature BDNF from proBDNF due to the limitation of specific antibodies. Recent studies have shown that proBDNF is a potent tumour suppressor (13,14). We previously generated specific antibodies to mature BDNF and proBDNF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophins are overexpressed in cancer (77) and implicated in neurodegeneration and inflammation (78). Sortilin binds via the C terminus of progranulin, suggesting that the C-terminal granulin domain can potentially mediate the binding even after proteolytic cleavage.…”
Section: What Is the Progranulin Receptor?mentioning
confidence: 99%
“…Increased BDNF and TrkB expressions have recently been found in several human tumors (13)(14)(15). BDNF/TrkB promote cancer cell survival and resistance to chemotherapy, while small-molecule inhibitors of Trk, such as K252α, inhibit cell growth and induce apoptotic death in cancer cells (16)(17)(18)(19). TrkB expression has been described in ovarian and cervical cancers (20,21), while being associated with a shorter survival and the promotion of metastasis in ovarian cancer patients (20 in cell proliferation, migration and suppression of anoikis (22,23).…”
Section: Introductionmentioning
confidence: 99%